Periodontal health status in patients with lung cancer: Case–control study - Singh, Pooja; Verma, Umesh Pratap; Verma, Ajay Kumar; Gupta, Prashant; Pathak, Anjani Kumar; Singhal, Rameshwari; Kaushal, Shalini (International Journal of Health Sciences, 2023)
Objective: The objective of this study was to assess the periodontal health status of individuals with lung cancer in the North Indian population. In addition, the study aimed to determine the levels of human beta-defensin2 (Hbd-2) in the gingival crevicular fluid (GCF) and serum samples collected from the participants. Methods: The study consisted of a total of 90 participants, who were categorized into three groups: Group 1 included 30 healthy individuals, Group 2 comprised 30 patients with chronic periodontitis, and Group 3 involved 30 patients diagnosed with both lung cancer and chronic periodontitis. Various periodontal parameters, including plaque index, gingival index, probing pocket depth, and clinical attachment level (CAL), were assessed in addition to the analysis of human beta defensin2 levels in both the GCF and serum samples of all participants. Results: The study results revealed that all clinical parameters assessed were higher in Group 3 compared to both Group 2 and Group 1. Specifically, the levels of hBD-2 in the GCF were measured as 52.29 ± 46.41 pg/mL in Group 1, 27.15 ± 28.76 pg/mL in Group 2, and 86.01 ± 68.82 pg/mL in Group 3. When comparing the hBD-2 levels in serum, the values were found to be 813.72 ± 269.43 pg/mL in Group 1, 591.50 ± 263.91 pg/mL in Group 2, and 1093.04 ± 674.55 pg/mL in Group 3. These intergroup comparisons indicate variations in hBD-2 levels among the different groups. Conclusions: The study findings demonstrated significantly higher clinical and biochemical markers in patients with both lung cancer and chronic periodontitis, in comparison to individuals with chronic periodontitis alone and healthy participants. These results suggest that Hbd-2 could potentially serve as a valuable diagnostic biomarker for identifying and distinguishing individuals with both lung cancer and chronic periodontitis.